Attraction is altered via modulation of the medial prefrontal cortex without explicit knowledge - Zorns, Samantha; Sierzputowski, Claudia; Ash, Sydney; Skowron, Molly; Minervini, Anthony; LaVarco, Adriana; Pardillo, Matthew; Keenan, Julian Paul (Frontiers in Human Neuroscience, 2024)
Previous studies have demonstrated that brain stimulation can alter an individual's physical appearance via dysregulation of the medial prefrontal cortex (MPFC). In this study, we attempted to determine if individuals who receive repetitive transcranial magnetic stimulation (rTMS) delivered to the MPFC were rated as more attractive by others. It has been previously reported that 1 hertz (Hz) (inhibitory) TMS can alter one's facial expressions such that frontal cortex inhibition can increase expressiveness. These alterations, detected by external observation, remain below the level of awareness of the subject itself. In Phase I, subjects (N = 10) received MPFC rTMS and had their photographs taken after each of the five stimulation conditions, in addition to making self-ratings across a number of variables, including attractiveness. In Phase II, participants (N = 430) rated five pictures of each of the Phase 1 individuals on attractiveness. It was found that there were no significant differences in self-assessment following rTMS (Phase I). However, attractiveness ratings differed significantly in Phase II. There was a significant difference found between 10 Hz TMS delivered to the MPFC (p < 0.001), such that individuals were rated as less attractive. Furthermore, 1 Hz TMS to the MPFC increased the number of ‘Most Attractive' ratings, while 10Hz TMS decreased the number of ‘Most Attractive' ratings (p < 0.001). These results suggest that the MPFC plays a role in attractiveness ratings to others. These data also support research showing that one's appearance can be altered below the level of awareness via rTMS. To our knowledge, this is the first investigation to examine how brain stimulation influences one's attractiveness.